Rancang Bangun Sistem Informasi Laboratorium Jurusan Ilmu Komputer Universitas Lampung - Putra, Ully Kharisma; Kurniawan, Didik; Hijriani, Astria (Universitas Lampung, 2016)
The computer lab is a place of experimentation, training, or research related to computer science and have several computers in a network that is used by certain circles. One usability labs Department of Computer Science, University of Lampung, namely as the venue for the practicum organized by an assistant professor with the participants called praktikan. The problem faced is the loss of computer lab files presence and value. This is quite disturbing reporting lab.The system created to administer the practical activities of the subsystems within it, namely subsystem schedules, presence subsystems, and subsystems value. This information system has the master data that can be processed by each of these subsystems, namely the login data, the data of the school year, the data study program, the student data, the data subjects, the data space, class data, the data plotting, the data lab, and data assistant. Information produced include a data assistant, courses, schedules, presence practicum and practical value.Keywords:Blackbox Testing, Equivalence Partitioning, Sistem Informasi, Software,Waterfall